Students’ Aesthetic Experiences in Performing Realistic Activities of Geometric Transformations - Shahmohammadi , Maryam; Aminifar, Elahe (Assessment and Practice in Educational Sciences, 2024)
Diverse learners require education with a planned aesthetic to experience beautiful phenomena in mathematics. To do so, we designed an educational program based on aesthetic experiences for high school seniors in the eleventh grade for four months. We used Charmaz’s constructivist grounded theory and a qualitative approach. We collected data through observation, recorded dialogues, and semi-structured interviews. We explain students’ beliefs about the beauty of geometric transformations and the stages of logical thought required to perform associated activities. The findings indicate that the course based on the aesthetic experience of geometric transformations assists students in thinking about its nature aesthetically. The results also reveal aesthetic components as a medium for students to discuss mathematical ideas and develop logical thinking skills. We present the research outcome as a visual model to illustrate the relationship between geometric transformations, aesthetic experiences, logical thinking, and aesthetic beliefs.